The Role and Importance of Characterization in the Interpretation of Literary Characters - Stakić, Mirjana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The interpretation of a literary work and the analysis of literary characters in the teaching of literature at all levels of education is based on the interpretation of characters' relation to the rest of the depicted artistic theme of a literary text and the examination of artistic means which an author used to create and characterize them. To become able to  interpret a literary work, a teacher practitioner has to possess theoretical knowledge of classification and numerous ways of characterization of literary characters. Theoretical and methodical literature describes plenty of methods of artistic characterization. Considering the importance to a practitioner of not only their theoretical knowledge, but also the ability of the practical application of this knowledge, we investigated what role and significance various methods of characterization have during the analysis of a literary text. The interpretation of a literary work requires a systematic and comprehensive approach in the interpretation of literary characters, and the particularities of the characterization itself condition and direct the way of interpretative approach. It is aligned with  them, in order to highlight and interpret, in the most functional, methodological, and justified way, all the particularities of characters as focal points of a plot, and representatives of meaning, aesthetic, and ethical values of a literary text, and interpret in that way the other more important segments of a literary work as a complex and multilayered structure.
Keywords: literary text; interpretation; characterization of literary characters; classification of literary characters; literary character